Orientasi kewirausahaan terhadap keberlanjutan usaha kerajinan pandai besi di Kecamatan Tellu Limpoe Kabupaten Sidrap - Herminawaty Abubakar; Nurhidayanti S. (DEDIKASI, 2020)
The existence of traditional blacksmith craftsmen in Tellu Limpoe Subdistrict, Sidrap Regency is now threatened with being displaced by machine technology. Constraints faced by blacksmith craftsmen are raw materials and equipment that are still traditional, capital production costs, raw materials that are difficult to obtain, have not been able to take advantage of advances in information and technology and market competition. The production technology used by blacksmiths is still conventional and is a hereditary skill, as well as the design has not been market oriented, so the quality of the products produced cannot compete especially with similar products produced by industries that have used modern technology. This service aims to improve the welfare of blacksmith craftsmen and the community in Tellu Limpoe District so that this handicraft business can survive amid competition in factory production. The method used in this service is in the form of socialization, training, mentoring and guidance of blacksmith craftsmen. The results of devotion in the form of mindset changes, increased managerial skills and increased income of blacksmith craftsmen.